Determinants of persistent malaria transmission in the Arjo-Didessa farm area in Ethiopia - Hiwot S. Taffese; Sibusiso M. Zuma (Southern African Journal of Infectious Diseases)
Background: In tropical and subtropical areas of the world, malaria is still a serious public health concern. Activities related to agricultural development that involve irrigation schemes likely increase the risk of malaria in tropical and sub-Saharan African regions. Ethiopia is a sub-Saharan country where malaria is endemic.